Grading and price in the accommodation sector of South Africa - Du Plessis, Engelina; Saayman, Melville (University of the Free State, 2011)
This article analyses the relationship between grading and price in the accommodation sector in South Africa. The literature review investigates whether the accommodation grading system is a good indicator of accommodation quality, and whether tourists get what they are paying for. The research was conducted in cooperation with the major role players in the accommodation sector in South Africa, namely the South African Tourism Service Association, the Federated Hospitality Association of Southern Africa and the Tourism Grading Council of South Africa. The results show a strong correlation between the grading of the accommodation and price. This confirms that managers also consider “stars” as symbols of the type of quality which they can use to communicate a “value for money” experience when tourists choose accommodation at a certain price.

Hierdie artikel fokus op ’n analise van die verhouding tussen gradering en prys in die akkommodasie-sektor in Suid-Afrika. Die navorsing is uitgevoer in samewerking met die hoofrolspelers in die akkommodasie-sektor naamlik SATSA (South African Tourism Service Association), FEDHASA (Federated Hospitality Association of Southern Africa) en TGCSA (Tourism Grading Council of South Africa). Spearman Rank-korrelasie is uitgevoer en die resultate toon ’n sterk korrelasie tussen die gradering van die akkommodasie en prys. Dit bevestig dat bestuurders “sterre” as simbole van die tipe gehalte wat hulle kan aanwend om ’n “waarde-vir-geld”-ervaring aan te dui wanneer toeriste akkommodasie teen ’n bepaalde prys kies.
Keywords: Accommodation grading system; South African Tourism Service Association; Federated Hospitality Association of Southern Africa; Tourism Grading Council of South Africa; Tourism industry